2019
DOI: 10.12659/msm.912785
|View full text |Cite
|
Sign up to set email alerts
|

Short-Foot Exercise Promotes Quantitative Somatosensory Function in Ankle Instability: A Randomized Controlled Trial

Abstract: BackgroundAnkle sprain reduces capacity for neurosensory information processing, and these patients commonly progress to chronic ankle instability (CAI). To address this problem, the short-foot exercise (SFE) may be used. However, there has been no previous research on the neurosensory impact of SFE.Therefore, the aim of this study was to assess improvement of quantitative neurosensory indicators after SFE and to determine the effect of proprioceptive sensory exercise (PSE) in patients with CAI.Material/Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 59 publications
1
64
0
21
Order By: Relevance
“…Sample size estimation for this study was based upon the results from two previous studies [ 15 , 19 ]. One study demonstrated that 24 sessions of SFE improved joint position sense in people with CAI as compared to proprioceptive sensory exercise; that is, those who received SFE had 20 ± 14% greater improvement [ 19 ]. The other study demonstrated that 10 sessions of tDCS targeting M1 in combination with eccentric ankle exercises induced improvement in the performance of dynamic balance test in people with CAI as compared to the sham.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size estimation for this study was based upon the results from two previous studies [ 15 , 19 ]. One study demonstrated that 24 sessions of SFE improved joint position sense in people with CAI as compared to proprioceptive sensory exercise; that is, those who received SFE had 20 ± 14% greater improvement [ 19 ]. The other study demonstrated that 10 sessions of tDCS targeting M1 in combination with eccentric ankle exercises induced improvement in the performance of dynamic balance test in people with CAI as compared to the sham.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of the SFE was to shorten the foot in the anterior–posterior direction by drawing the metatarsals to the heel without flexing the toes. This relatively novel proprioception training strategy has been shown to improve foot muscle strength and dynamic stability more than conventional proprioceptive sensory exercise [ 19 ]. Four blocks of SFE were completed during each 20 min HD-tDCS or sham stimulation session.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is necessary to understand which type of exercise or protocol is more efficient and has better cost-benefit results. In this sense, diverse works have defended the SFE when compared to other types of training centered on improving the short plantar muscle [1,3,25,29,30] such as toe curl activity exercises [17], proprioceptive sensory exercises [26], and "Vele's Forward Lean" and "Reverse Tandem Gait" [1]. Lee at al.…”
Section: Discussionmentioning
confidence: 99%
“…The active and neural subsystems are important in maintaining standing balance and controlling body posture [3]. Impaired movement sense and reduced foot muscle strength increase walking variability, fall risk [4,5], and even sports-related injuries such as plantar fasciitis and chronic ankle instability (CAI) [6,7]. Therefore, many studies have focused on strengthening the foot core system to prevent foot injuries.…”
Section: Introductionmentioning
confidence: 99%